Characterization of plasma and emergent ion beam in a compact helicon source with permanent magnets - Virko, Yu.V.; Virko, V.F.; Shamrai, K.P.; Yakimenko, A.I. (Вопросы атомной науки и техники, 2007)
A compact helicon source with multi-component changeable magnetic system was studied to gain enhanced parameters of plasma and emergent ion beam. Alteration of the magnetic field configuration was found to be the main instrument for increasing the plasma density and ion beam current. The source efficiency was also critically dependent on the rf antenna position and Ar gas pressure. By optimizing these parameters, plasma outflow was greatly increased and the emergent ion beam of energy above 100 eV was produced.